EXPERIMENTAL ISSLEDOVANIYASHUMOVOGO REGIME SALTOVSKOE RESIDENTIAL AREA OF KHARKOV (Municipal economy of cities (Technical science), 2013)
The problem of improving existing tools to combat noise. One of the areas of its solutions - the study of the noise mode of urban areas.